Optimization of Renewable Energy Consumption in Charging Electric Vehicles Using Intelligent Algorithms - Reza Alayi; Alfian Ma'arif; Yaser Ebazadeh; Ferydon Gharadaghi; Farnaz Jahanbin; Nima Shafaghatian (Universitas Muhammadiyah Yogyakarta, 2022)
Today, due to the considerable growth of the power/electricity industry, the high distance between low and high loads, and also economic crisis plagued most of the countries in the world, the operation of power plants has been transformed into a vital issue. Also, increasing use of energy and lack of accountability of conventional resources in response to supply the need has created many problems, including a decrease of fossil fuel sources, adverse environmental impacts, and increase of Greenhouse Gases (GHGs) all around the world. The concerns induced by this problem have caused the technologies consistent with an environment such as Electric Vehicles (EVs) to attract more and more attention. According to the capability of two-side exchange of power in these vehicles, if a significant number of them are connected to a net under management and intelligent control of an institution consistently, they can behave such a virtual small power plant with high start-up speed and without any cost.